ENVIRONMENTAL ISSUES IN FORMING SITES OF FOUNDRY SHOPS AND THE WAYS OF SOLUTION - Z. A. Neson; Yu. Yu. Guminskiy (Литьë и металлургия)
The major factors having an detrimental harmful impact on ecology in forming sites in foundry shops are examined in the article. The well-known ways of solution of these issues are described and the new ways of solution are proposed. The general approach to the solution of environmental issues on forming sites of foundry shops is formulated.